A bibliometric insight into nanomaterials in vaccine: trends, collaborations, and future avenues - Wu, Beibei; Liu, Ye; Zhang, Xuexue; Luo, Ding; Wang, Xuejie; Qiao, Chen; Liu, Jian (Frontiers in Immunology, 2024)
Background: The emergence of nanotechnology has injected new vigor into vaccine research. Nanovaccine research has witnessed exponential growth in recent years; yet, a comprehensive analysis of related publications has been notably absent. Objective: This study utilizes bibliometric methodologies to reveal the evolution of themes and the distribution of nanovaccine research. Methods: Using tools such as VOSviewer, CiteSpace, Scimago Graphica, Pajek, R-bibliometrix, and R packages for the bibliometric analysis and visualization of literature retrieved from the Web of Science database. Results: Nanovaccine research commenced in 1981. The publication volume exponentially increased, notably in 2021. Leading contributors include the United States, the Chinese Academy of Sciences, the "Vaccine", and researcher Zhao Kai. Other significant contributors comprise China, the University of California, San Diego, Veronique Preat, the Journal of Controlled Release, and the National Natural Science Foundation of China. The USA functions as a central hub for international cooperation. The USA acts as a central hub for international cooperation Financial support plays a pivotal role in driving research advancements. Key themes in highly cited articles include vaccine carrier design, cancer vaccines, nanomaterial properties, and COVID-19 vaccines. Among 7402 keywords, the principal nanocarriers include Chitosan, virus-like particles, gold nanoparticles, PLGA, and lipid nanoparticles. Nanovaccine is primarily intended to address diseases including SARS-CoV-2, cancer, influenza, and HIV. Clustering analysis of co-citation networks identifies 9 primary clusters, vividly illustrating the evolution of research themes over different periods. Co-citation bursts indicate that cancer vaccines, COVID-19 vaccines, and mRNA vaccines are pivotal areas of focus for current and future research in nanovaccines. "candidate vaccines," "protein nanoparticle," "cationic lipids," "ionizable lipids," "machine learning," "long-term storage," "personalized cancer vaccines," "neoantigens," "outer membrane vesicles," "in situ nanovaccine," and "biomimetic nanotechnologies" stand out as research interest. Conclusions: This analysis emphasizes the increasing scholarly interest in nanovaccine research and highlights pivotal recent research themes such as cancer and COVID-19 vaccines, with lipid nanoparticle-mRNA vaccines leading novel research directions.